Folded network and structural transition in molten tin - Xu, Liang; Wang, Zhigang; Chen, Jian; Chen, Songyi; Yang, Wenge; Ren, Yang; Zuo, Xiaobing; Zeng, Jianrong; Wu, Qiang; Sheng, Howard (Nature communications, 2022)
The fundamental relationships between the structure and properties of liquids are far from being well understood. For instance, the structural origins of many liquid anomalies still remain unclear, but liquid-liquid transitions (LLT) are believed to hold a key. However, experimental demonstrations of LLTs have been rather challenging. Here, we report experimental and theoretical evidence of a second-order-like LLT in molten tin, one which favors a percolating covalent bond network at high temperatures. The observed structural transition originates from the fluctuating metallic/covalent behavior of atomic bonding, and consequently a new paradigm of liquid structure emerges. The liquid structure, described in the form of a folded network, bridges two well-established structural models for disordered systems, i.e., the random packing of hard-spheres and a continuous random network, offering a large structural midground for liquids and glasses. Our findings provide an unparalleled physical picture of the atomic arrangement for a plethora of liquids, shedding light on the thermodynamic and dynamic anomalies of liquids but also entailing far-reaching implications for studying liquid polyamorphism and dynamical transitions in liquids. Unraveling the structural origin of liquid anomalies remains a challenging topic. Xu et al. propose a folded-network structural model for molten tin and provide insights into the observed second-order-like structural transition.